Evaluation of a push-pull strategy against fungus gnats (Diptera: Sciaridae) - Diderot, Therese (SLU/Dept. of Biosystems and Technology (from 130101), 2016)
Fungus gnats (Diptera: Sciaridae) are major insect pests in greenhouse production systems. Their larvae reside in the growing medium and can cause severe damage on the plants when feeding on the root system. When the fungus gnats occur at high population densities, the damage can inhibit plant growth, or in worst-case kill the plant entirely. Moreover, both adult and larva are capable of spreading certain diseases within the greenhouse. There is a need for new methods to supplement the current integrated pest management, and one alternative is to use odours that repel fungus gnats from the growing area. A push-pull strategy was developed using essential oil of peppermint (Mentha piperita) to repel the fungus gnats, and yellow sticky card traps to attract and kill them. An experiment was conducted to evaluate the potential of using this strategy to diminish the fungus gnat population in organic greenhouse production of basil (Ocimum basilicum). Furthermore, the experiment tested if it was possible to enhance the effect of the strategy by equipping the yellow sticky cards with green light-emitting diods (LED). The results show that the push-pull strategy was successful in reducing the number of fungus gnats in the treated areas. However, the effect of the strategy was not enhanced by equipping the yellow sticky cards with green LEDs.